Ghost galleon : the discovery and archaeology of the San Juanillo on the shores of Baja California - Von der Porten, Edward P. (Ed Rachal Foundation nautical archaeology series., 2019)
"An inside view of how archaeologists, working like detectives at an ancient crime scene, carefully assemble the evidence that allows scientific reconstruction of events from the distant past. In a series of expeditions from 1999 to 2016, Von der Porten and his dedicated team, in association with the Instituto Nacional de Antropología e Historia (INAH), assembled scores of artifacts, conducted countless hours of archival and other research, and finally concluded that they had located the buried remains of the cargo from the sixteenth century Manila galleon 'San Juanillo' on the shores of Baja California"--Provided by publisher.